Polluted water, stinking water, frozen water, no water: A life threatening situation! Perspectives from Exodus 1-11 and 15-17 - Van der Walt, Steven (Stellenbosch Theological Journal, 2016)
The article highlights the life threatening consequences Israel could have faced if they did not stay within the creational rhythm which YHWH planned for them. Natural phenomena, in which water played a significant role, contributed to these life threatening circumstances. Certain pericopes of two external narratives (Ex 1-14; Ex 15-18) form the backbone of this article. Natural phenomena (transformation of water) are being used to highlight the fact that YHWH alone is creator God: live according to His ordinances (rhythm) and be assure to be blessed; do not live accordingly, and be assure that the natural rhythm of nature could turn upside down with devastating consequences such as polluted water, stinking water, frozen water or, no water at all. It turns out that being without life-giving water is just as dangerous as being without YHWH, thus a life threatening situation.